2014
DOI: 10.1165/rcmb.2013-0320oc
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Chaperones Mitigate Experimental Asthma by Attenuating Endoplasmic Reticulum Stress

Abstract: Endoplasmic reticulum (ER) stress and consequent unfolded protein response (UPR) are important in inflammation but have been poorly explored in asthma. We used a mouse model of allergic airway inflammation (AAI) with features of asthma to understand the role of ER stress and to explore potential therapeutic effects of inhaled chemical chaperones, which are small molecules that can promote protein folding and diminish UPR. UPR markers were initially measured on alternate days during a 7-day daily allergen chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 43 publications
0
39
0
Order By: Relevance
“…Recently, ER/SR stress markers have been identified in lungs from mouse models of airway diseases and chemical chaperones. Inhibition of ER/SR stress responses successfully reduced airway inflammation and airway hyper-reactivity observed in those models (Hoffman et al 2013; Kim et al 2013; Makhija et al 2013). The results of our studies on hASM cells support a central role of inflammatory cytokine-induced ER/SR stress in both the enhanced contractile response of ASM (hyper-reactive state) and the increase in ASM cell proliferation (synthetic state) (Fig.…”
Section: Er/sr Stress In Asm Provides Potential Therapeutic Targets Fmentioning
confidence: 88%
See 1 more Smart Citation
“…Recently, ER/SR stress markers have been identified in lungs from mouse models of airway diseases and chemical chaperones. Inhibition of ER/SR stress responses successfully reduced airway inflammation and airway hyper-reactivity observed in those models (Hoffman et al 2013; Kim et al 2013; Makhija et al 2013). The results of our studies on hASM cells support a central role of inflammatory cytokine-induced ER/SR stress in both the enhanced contractile response of ASM (hyper-reactive state) and the increase in ASM cell proliferation (synthetic state) (Fig.…”
Section: Er/sr Stress In Asm Provides Potential Therapeutic Targets Fmentioning
confidence: 88%
“…A recent study (Makhija et al 2013) showed that there is an increased expression of ER/SR stress protein markers such as BiP/GRP-78 and ATF6 in lungs from an ovalbumin (OVA) sensitized mouse model of asthma, and that chemical chaperone treatment used to attenuate ER/SR stress is effective in reducing airway remodeling and inflammation. Others recent studies confirmed the presence of ER/SR stress markers in the OVA mouse model (Kim et al 2013) as well as another mouse model of asthma: house dust mite sensitization (Hoffman et al 2013).…”
Section: Cytokine-induced Er/sr Stress and The Unfolded Protein Respomentioning
confidence: 99%
“…IRE1α-or IRE1β-mediated XBP-1 activation may sustain the enhanced ER calcium stores frequently observed in inflamed airway mucosa (209), as well as the IL-13-driven excessive airway epithelial mucus production observed in allergic airway disease. However, a recent study demonstrated that chemical chaperones dose-dependently reduce UPR gene expression and inflammatory markers (210). Robust genetic studies will be critical to confidently determine whether and how the observed UPR activation contributes to inflammatory …”
Section: Lung Diseasementioning
confidence: 99%
“…Furthermore, TMAO has been found to protect epidermolysis bullosa simplex keratinocytes from heat stressinduced keratin aggregation, which implies the therapeutic potential of TMAO in epidermolysis M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 15 bullosa and other keratinopathies [85]. Other potential therapeutic applications of TMAO include corneal dystrophies [86], cataract [87], glaucoma [88], asthma [89] or Machado-Joseph disease/spinocerebellar ataxia-3 (MJD/SCA-3) [90].…”
Section: Tmao As a Therapeutic Agentmentioning
confidence: 99%